Amoebiasis - Entamoeba Histolytica Infections: A Review - Rees, P.H. (East African Medical Journal, 1986)
Many populations of Entamoeba histolytica, identified by enzyme electrophoresis, are non-pathogenic, and as infections are frequently self limiting, treatment of asymptomatic cyst' passers may often be unnecessary. Tissue (invasive) amoebiasis remains a diagnostic challenge, but the advent of improved serology and , for liver abscess, scannning techniques, particularly ultrasound, has made it easier to come to a reasonably certain diagnosis before starting treatment. Where facilities are limited, a therapeutic trial with a nitroimidazole such as metronidazole in an adequate single daily dose for 3 days is safe and rapidly effective.
Keywords: Enzyme electrophoresis; Asymptomatic cyst; Nitroimidazole; Metronidazole; Hydatid cyst